Effect of Probiotic (Saccharomyces cerevisiae) Supplemented Poultry Diet on the Lymphoid Organs, Hematology and Production Parameters of Broiler Chickens - Ezema, Arinzechukwu Stephen; Ugwu, Patience Chinasa; Njoku, Esther; Edeh, Miracle Emeka; Ezema, Chuka (International Journal of Poultry Science, 2025)
Objective: The aim of the study was to evaluate the effect of poultry diet supplemented with Saccharomyces cerevisiae on lymphoid organs, weight gain and hematology of broilers. Materials and Methods: A total of 60 day-old broiler chicks (Ross 308) were randomly divided into two groups (A- control and B- probiotic) of 30 birds each. Each group was further subdivided into 3 replicates of 10 birds each. Birds were fed ad libitum. At the 6th week, 2 birds from each replicate were randomly selected and 3 mL of blood was collected from the right jugular vein for haematological analysis. The thymus, spleen and ileum was collected for histopathology. The weight gain, feed intake and feed conversion ratio were also determined. Results: Birds in group B showed increased proliferation of cells in the thymus, spleen and Peyer's patches. The absolute heterophil count of birds in Group A (11.577×103 μL) was significantly (p